La destilación por arrastre de vapor como estrategia metodológica para fortalecer el aprendizaje sobre la obtención de aceites esenciales a partir de plantas medicinales y aromáticas con los estudiantes de tercer año de bachillerato paralelo A , del colegio Vilcabamba, de la parroquia del mismo nombre, cantón Loja, periodo académico 2013 – 2014 - Aguilera Ochoa, Anabel Bernarda (2015)
Organic Chemistry is an experimental science, and as such the laboratory work is of paramount importance to the teaching - learning this subject. For laboratory practices constitute the main axis for proper practical relation theory, so that the main purpose is for students to develop their own skills and abilities of the experimental method and scientific research, broaden , deepen , consolidate , generalize and check the theoretical foundations of the discipline through experimentation.(Freire, 2010, pág. 6) The research aimed to study THE DISTILLATION BY STEAM AS A METHODOLOGY STRATEGY TO STRENGTHEN LEARNING ABOUT OF ESSENTIAL OILS FROM MEDICINAL AND AROMATIC PLANTS WITH STUDENTS OF THIRD YEAR OF PARALLEL BACHELOR " A " OF “VILCABAMBA” HIGHSCHOOL PARISH OF THE SAME NAME , CANTON Loja , ACADEMIC PERIOD 2013 – 2014 The general objective was raised for this research was : Apply the distillation by steam as a methodology strategy to strengthen learning about of essential oils from medicinal and aromatic plants with students of third year of parallel bachelor " A " of “Vilcabamba” highschool parish of the same name , canton Loja , academic period 2013 – 2014 In the development of this research took into account the following methods: analytical, descriptive, inductive, deductive and method of Pearson linear correlation. I used the survey as technique and instrument of data collection and information. With the analysis, discussion and interpretation of the data was found that students do not have a clear understanding of the concept of essential oils, this problem determines the level of understanding of the concept of essential oil is elementary; they don´t performe in laboratory to obtain essential oils from medicinal and aromatic plants using distillation by steam.